Amino acids and endurance exercise - Hargreaves, M.; Snow, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
Although skeletal muscle is capable of oxidizing selected amino acids, exercise in the fed and carbohydrate-replete condition results in only a small increase in amino acid utilization. Nevertheless, it may be important to increase the dietary protein requirements of active individuals. There is ongoing debate as to whether the amino acids for oxidation are derived from the free amino acid pool, from net protein breakdown, or a combination of both. There has been interest in the potential ergogenic benefits of amino acid ingestion; however, BCAA ingestion does not appear to affect fatigue during prolonged exercise, there is little support from controlled studies to recommend glutamine ingestion for enhanced immune function, and although glutamine stimulates muscle glycogen synthesis, its addition to carbohydrate supplements provides no additional benefit over ingestion of carbohydrate alone.